Does Governance Efficiency Affect Equity Agency Costs? Evidence from Borsa Istanbul - Aras, Guler; Furtuna, Ozlem Kutlu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
In this article, we investigate whether the governance efficiency variables mitigate the costs arising from agency problems for companies listed on the Borsa Istanbul (BIST). The empirical analyses are conducted on nonfinancial firms during the 2005-11 period. Four models have been implemented for each of the agency-cost proxies, and all of them are estimated by panel data regressions with fixed effects. This study provides evidence from an emerging market about which governance variables and control variables differently reduce the extent of conflicts of interest between managers and shareholders. The findings also indicate that highly concentrated firms in Turkey are more engaged with agency problems and do not effectively control excessive perquisite consumption and facilitate asset utilization.
Keywords: agency cost; Borsa Istanbul; corporate governance; emerging markets; OWNERSHIP STRUCTURE; BOARD COMPOSITION; PERFORMANCE; FIRM; MECHANISMS; Business & Economics; International Relations